1994
DOI: 10.1051/rnd:19940105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3 chemical treatments on in vitro fermentation of rice straw by mixed rumen microbes in the presence or absence of anaerobic rumen fungi

Abstract: Summary ― Rice straw (Rs) was treated by a sodium chlorite/acetic acid mixture (Sct), ammoniation (At) and alkaline hydrogen peroxide (Athp) methods. The objective was to compare their degradation and fermentation products in the presence or suppression of anaerobic fungi. Significant differences (P< 0.01) in degradation of straws were observed during all periods of incubation with Sct having the highest digestibilities during the 48-h and 72-h incubations. The degradation of Sct straw was highest in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Using aerobic and anaerobic fungi as pretreatment agents resulted in increased biodegradability of rice straw (Ghosh and Bhattacharyya 1999;Cann et al 1994). Methane production from rice straw AD was increased 31-46% when pretreating it with white-rot fungus and brown-rot fungus (Polyporus ostreiformis using a strawto-fungi ratio of 14:1 and then digested in batch reactors at 30 °C after a 3-week incubation period.…”
Section: Biological Pretreatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Using aerobic and anaerobic fungi as pretreatment agents resulted in increased biodegradability of rice straw (Ghosh and Bhattacharyya 1999;Cann et al 1994). Methane production from rice straw AD was increased 31-46% when pretreating it with white-rot fungus and brown-rot fungus (Polyporus ostreiformis using a strawto-fungi ratio of 14:1 and then digested in batch reactors at 30 °C after a 3-week incubation period.…”
Section: Biological Pretreatmentmentioning
confidence: 99%
“…Methane production from rice straw AD was increased 31-46% when pretreating it with white-rot fungus and brown-rot fungus (Polyporus ostreiformis using a strawto-fungi ratio of 14:1 and then digested in batch reactors at 30 °C after a 3-week incubation period. Cann et al (1994) reported that the anaerobic fungi from the rumen consistently increased the digestibility of rice straw when compared with fermenters where the fungi were inhibited. Haruta et al (2002) also presented the enhancements by a microbial community formed by mixing rice straw, chicken feces, pig feces, cattle feces, and sugarcane dregs.…”
Section: Biological Pretreatmentmentioning
confidence: 99%